A Meta-Analysis of the Factor Structure of the Classroom Assessment Scoring System (CLASS). Issue 2 (3rd February 2020) - Li, Hongli; Liu, Jingxuan; Hunter, Charles Vincent
Abstract: The Classroom Assessment Scoring System (CLASS) has been used extensively to measure teacher-student interactions and classroom quality. With a theoretical foundation rooted in the developmental theory of learning, CLASS has three primary domains—Emotional Support, Classroom Organization, and Instructional Support. In this study, we performed a meta-analysis of the factor structure of CLASS using Cheung's two-stage structural equation modeling (TSSEM) approach. After searching the literature, we obtained 26 correlation matrices of the 10 dimensions shared by multiple versions of CLASS. This meta-analysis supports the three-factor model initially proposed by CLASS developers. The finding of this meta-analysis provides important evidence pertinent to the CLASS factor structure and has significant implications regarding the interpretation and use of CLASS scores.